2017
DOI: 10.6018/analesps.33.3.260811
|View full text |Cite
|
Sign up to set email alerts
|

Emotional experience in individual and cooperative traditional games. A gender perspective.

Abstract: <p>This study explored the effect of gender (GE) and group gender composition (GGEC) on men’s and women’s experiences of emotions when taking part in different games. To formulate our hypotheses we used a theoretical framework formed by the theories of Lazarus and Bisquerra on the construct of emotional competence and well-being and their relationship with gender stereotypes, Parlebas’s motor action theory and previous results of empirical research related to games, emotions and gender relations. The par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
4
13
0
3
Order By: Relevance
“…The motivational profile of the students reveals that the sports record must be known, as well as the gender, in the initiation to basketball. Some experiences have helped to specify a gender profile (Kivikangas, Kätsyri, Järvelä, & Ravaja, 2014), with numerous contributions from the motor game (Lagardera & Lavega, 2011), confirming that boys experienced mostly negative emotions with greater intensity (Muñoz et al, 2017;Lavega et al, 2017) while girls experimented more intensely positive emotions . A study that started from games of cooperation, opposition, psychomotor and cooperation-opposition concluded without finding emotional differences among students because of gender (Lavega, Filella, Lagardera, Mateu, & Ochoa, 2013), in line with the study we present in relation to emotions.…”
Section: Discussionmentioning
confidence: 99%
“…The motivational profile of the students reveals that the sports record must be known, as well as the gender, in the initiation to basketball. Some experiences have helped to specify a gender profile (Kivikangas, Kätsyri, Järvelä, & Ravaja, 2014), with numerous contributions from the motor game (Lagardera & Lavega, 2011), confirming that boys experienced mostly negative emotions with greater intensity (Muñoz et al, 2017;Lavega et al, 2017) while girls experimented more intensely positive emotions . A study that started from games of cooperation, opposition, psychomotor and cooperation-opposition concluded without finding emotional differences among students because of gender (Lavega, Filella, Lagardera, Mateu, & Ochoa, 2013), in line with the study we present in relation to emotions.…”
Section: Discussionmentioning
confidence: 99%
“…This first level of analysis was used to study the predictive capacity of variables internal to the games, such as domains of motor action (psychomotor, cooperation, opposition, 5 CIENCIAS HUMANAS Y SOCIALES -FORO "JOSÉ MARÍA CAGIGAL" | SOCIAL SCIENCES -"JOSÉ MARÍA CAGIGAL" FORUM Metodología cualitativa en el estudio del juego tradicional | Qualitative Methodology in the Study of Traditional Games de oposición, de cooperación-oposición), competición (ganar, perder, no competir), así como externas a los juegos: género (masculino, femenino), historial deportivo (con o sin historial), organización del alumnado (grupos mixtos o segregados). Se ha observado que los dominios de acción motriz y el factor competición funcionan como las variables predictivas más potentes para explicar el bienestar o malestar (Duran & Costes, 2018;Duran et al, 2014;Lavega et al, 2017;Muñoz et al, 2017). Estos primeros resultados estadísticos, resultantes del primer nivel de análisis, se han visto enriquecidos mediante la estrategia metodológica de métodos mixtos.…”
Section: Consequences Of the Qualitative Methodology Appliedunclassified
“…La construcción del mapa emocional no debe confundirse con la realidad pero sí ayuda, y no poco, a que los profesionales de la docencia orienten los procedimientos utilizados en base a los dominios de acción motriz para cooperation-opposition) and competition (winning, losing, not competing), and external to the games, such as gender (male, female), sports background (with or without a background in sports) or student organization (coed or segregated groups). It was observed that the domains of motor action and the competition factor operated as the most powerful predictive variables for explaining wellbeing or discomfiture (Duran & Costes, 2018;Duran et al, 2014;Lavega et al, 2017;Muñoz et al, 2017). These preliminary statistical results from the first level of analysis were enriched through the methodological strategy of mixed methods.…”
Section: Consequences Of the Qualitative Methodology Appliedmentioning
confidence: 99%
See 2 more Smart Citations